1998
DOI: 10.1007/s002709900211
|View full text |Cite
|
Sign up to set email alerts
|

Local Intravascular Drug Delivery: In Vitro Comparison of Three Catheter Systems

Abstract: Different catheter designs lead to different patterns of local drug delivery. The differences in penetration depth and amount of the substance delivered to the vessel wall should be known and might be useful for targeting specific areas within the vessel wall.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…So far, several preclinical studies reported the use of nanospheres to deliver limus derivatives, but to the best of our knowledge, none of them attempted everolimus delivery in the coronary territory 13,21‐23 . In the study of Granada et al, the authors evaluated feasibility of delivery, long‐term retention and vascular effects of sirolimus nanospheres delivered through a novel porous angioplasty balloon in normal porcine arteries 23 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…So far, several preclinical studies reported the use of nanospheres to deliver limus derivatives, but to the best of our knowledge, none of them attempted everolimus delivery in the coronary territory 13,21‐23 . In the study of Granada et al, the authors evaluated feasibility of delivery, long‐term retention and vascular effects of sirolimus nanospheres delivered through a novel porous angioplasty balloon in normal porcine arteries 23 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the nanospheres used in our study were designed to minimize their diameter, a key factor in the process of cell internalization 27 . Furthermore, to increase the success rate of short‐term nanospheres delivery, a microporous polytetrafluoroethylene Clearway RX balloon catheter was chosen, which has a proven efficacy of intra‐arterial drug application in previously published experimental studies 11‐13 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Local delivery of these agents can be accomplished using specialized catheters that employ passive, pressure-driven, electrically, or mechanically enhanced diffusion for delivery. 25, 26 Using these catheters for direct delivery of the agents only allows for one application or requires an indwelling line that is prone to thrombosis. A single application of reactive PEG that subsequently serves as a specific target for the drug or therapeutic vector to be systemically injected over time may prove to be a more suitable system for long-term delivery.…”
Section: Discussionmentioning
confidence: 99%